Mitigation of harmonic distortions in third rail electrical systems - Dick Sang Hoo; Kein Huat Chua; Yun Seng Lim; Boon Han Lim; Mohammad Babrdel Bonab; Li Wang (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The extensive use of power electronic converters in the third rail system increases the harmonic distortions on the rail electrical feeding systems. Electrical machines and transformers could be overheated causing premature failures of the devices. It is therefore important to address the harmonic distortions on the electrical networks during real-time operation, which includes the degraded operation, not just the normal operation. In this paper, the harmonic distortions of a third rail system are investigated using electrical transient and analysis program (ETAP) simulation software. Four operating scenarios, namely the normal operation and three degraded operations, are considered in the studies. The degraded operations occur when one of the bulk supply transformers or 33 kV feeders is out of service. The findings of the studies showed that the 11th and 13th order harmonics are the dominant harmonic orders due to the use of 12-pulse rectifiers on the third rail system. Single-tuned harmonic filters are designed and placed in the 33 kV feeders to mitigate the individual voltage harmonic distortion (IHDv) and the total voltage harmonic distortion (THDv) so that it is within the statutory of IEEE 519:2014.